APOE4 exacerbates synapse loss and neurodegeneration in Alzheimer’s disease patient iPSC-derived cerebral organoids - Zhao, Jing; Fu, Yuan; Yamazaki, Yu; Ren, Yingxue; Davis, Mary D.; Liu, Chia-Chen; Lu, Wenyan; Wang, Xue; Chen, Kai; Cherukuri, Yesesri; Jia, Lin; Martens, Yuka A.; et al. (Nature communications, 2020)
APOE4 is the strongest genetic risk factor associated with late-onset Alzheimer’s disease (AD). To address the underlying mechanism, we develop cerebral organoid models using induced pluripotent stem cells (iPSCs) with APOE ε3/ε3 or ε4/ε4 genotype from individuals with either normal cognition or AD dementia. Cerebral organoids from AD patients carrying APOE ε4/ε4 show greater apoptosis and decreased synaptic integrity. While AD patient-derived cerebral organoids have increased levels of Aβ and phosphorylated tau compared to healthy subject-derived cerebral organoids, APOE4 exacerbates tau pathology in both healthy subject-derived and AD patient-derived organoids. Transcriptomics analysis by RNA-sequencing reveals that cerebral organoids from AD patients are associated with an enhancement of stress granules and disrupted RNA metabolism. Importantly, isogenic conversion of APOE4 to APOE3 attenuates the APOE4 -related phenotypes in cerebral organoids from AD patients. Together, our study using human iPSC-organoids recapitulates APOE4 -related phenotypes and suggests APOE4 -related degenerative pathways contributing to AD pathogenesis. APOE4 is a strong genetic risk factor for late-onset Alzheimer’s disease. Here, the authors show that APOE4 is associated with AD features in hiPSCs-derived cerebral organoids. Isogenic conversion of APOE4 to APOE3 attenuates the AD-associated phenotype.